PROSES PEMBELAJARAN DARING DI SEKOLAH PADA MASA PANDEMI COVID-19 DI PROVINSI LAMPUNG - Marilin Kristina; Novi Ayu Kristiana Dewi; Noca Yolanda Sari (Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract: Online Learning Process at School The Covid-19 Pandemic Lampung Province This study aims to determine the online learning process and reveal the obstacles faced in online learning during the Covid-19 pandemic. This study uses a qualitative descriptive research method that aims to study intensively about the current problem or situation. The number of respondents from this study were 22 respondents spread across Lampung Province with education levels ranging from SD/Mi, SMP/MTs, and SMA/MA. The results of this study are students who do online learning tend to be uninterested and bored in doing learning. For students there are several obstacles and difficulties in participating in online learning, namely inadequate internet network, difficulty concentrating while participating in online learning, feeling bored, no parents accompanying online learning, unable to ask directly to the teacher, and not having digital devices in learning. online learning.